Stunting, wasting and breast-feeding as correlates of body composition in Cambodian children at 6 and 15 months of age. Issue 6 (11th February 2019) - Skau, Jutta K. H.; Grenov, Benedikte; Chamnan, Chhoun; Chea, Mary; Wieringa, Frank T.; Dijkhuizen, Marjoleine A.; Ritz, Christian; Wells, Jonathan C.; Berger, Jacques; Filteau, Suzanne; Roos, Nanna; Michaelsen, Kim F.; et al.
Abstract: The study aimed at assessing stunting, wasting and breast-feeding as correlates of body composition in Cambodian children. As part of a nutrition trial (ISRCTN19918531), fat mass (FM) and fat-free mass (FFM) were measured using 2 H dilution at 6 and 15 months of age. Of 419 infants enrolled, 98 % were breastfed, 15 % stunted and 4 % wasted at 6 months. At 15 months, 78 % were breastfed, 24 % stunted and 11 % wasted. Those not breastfed had lower FMI at 6 months but not at 15 months. Stunted children had lower FM at 6 months and lower FFM at 6 and 15 months compared with children with length-for-age z ≥0. Stunting was not associated with height-adjusted indexes fat mass index (FMI) or fat-free mass index (FFMI). Wasted children had lower FM, FFM, FMI and FFMI at 6 and 15 months compared with children with weight-for-length z (WLZ) ≥0. Generally, FFM and FFMI deficits increased with age, whereas FM and FMI deficits decreased, reflecting interactions between age and WLZ. For example, the FFM deficits were –0·99 (95 % CI –1·26, –0·72) kg at 6 months and –1·44 (95 % CI –1·69; –1·19) kg at 15 months (interaction, P <0·05), while the FMI deficits were –2·12 (95 % CI –2·53, –1·72) kg/m 2 at 6 months and –1·32 (95 % CI –1·77, –0·87) kg/m 2 at 15 months (interaction, P <0·05). This indicates that undernourished children preserve body fat at the detriment of fat-free tissue, which may have long-term consequences for health and working capacity.